2015
DOI: 10.1007/s10113-015-0905-z
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate sensitivity of wetland environments in Rwanda: the need for a location-specific approach

Abstract: Wetlands are sustaining large communities of people in Rwanda where 10 % of its land surface consists of many local wetlands. Sustainable future management of these numerous wetlands requires a reliable inventory of their location and a dynamic quantitative characterization that allows assessment of their climate change sensitivity. The aim of this study was to assess the importance of climatic factors for determining wetland location at different regional scales. Wetland locations were analyzed and statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Coffee competes with food crops for the limited land available. Agricultural land (including coffee) take up 54.2 % of the total country territory, the remaining 45.8 % comprise of forest (28.8 %), wetlands and water bodies (11 %) (Nyandwi et al 2016) and urban areas (6 %). As with other cropping systems, the spatial distribution of coffee is a function of environmental drivers (soil, climate and topography) and human drivers (demography, infrastructure, technology and institutions) Veldkamp & Fresco 1997;Verbist et al 2005;Hernandez-Martinez et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffee competes with food crops for the limited land available. Agricultural land (including coffee) take up 54.2 % of the total country territory, the remaining 45.8 % comprise of forest (28.8 %), wetlands and water bodies (11 %) (Nyandwi et al 2016) and urban areas (6 %). As with other cropping systems, the spatial distribution of coffee is a function of environmental drivers (soil, climate and topography) and human drivers (demography, infrastructure, technology and institutions) Veldkamp & Fresco 1997;Verbist et al 2005;Hernandez-Martinez et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Both approaches did not include neither socio-economic factors nor the potential dynamic climate factors making both approach not sensitive for the rapid changing Rwandan socio-economic conditions and the expected climate change. The later can be significant in the nearby future as illustrated by Nyandwi et al (2016) who demonstrated that an increase of 1 % in annual temperature can cause a net wetland area decline by 12 %, making these areas suitable for other land use. It is our objective to analyse the spatial coffee field distribution using the new high resolution coffee map (Mukashema et al 2014) and using available biophysical and socioeconomic factors that co-determine coffee cultivation locations in Rwanda.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial variables used for mapping coffee fields are the average diameter of the tree crown and the minimum size of the field. The diameter of the coffee tree crown is set to 2 m based on our knowledge of the coffee trees and their spacing across Rwanda whereas the size of the field is set to a minimum of 200 coffee trees following Nsengiyumva (2009) giving it the same minimum criterion as used in the national coffee census. Land use and topography variables were also considered to optimize the location of coffee within the landscape.…”
Section: Evidence Variables For Coffeementioning
confidence: 99%
“…(6) Reported coffee areas by the national coffee census of 2009. The census was conducted in all 30 districts of Rwanda by OCIR-CAFÉ together with Statistics Officers at the district and sector level (Nsengiyumva, 2009). …”
Section: Training and Validation Datasetmentioning
confidence: 99%
See 1 more Smart Citation